Low-Dose 5-Aza and DZnep Alleviate Acute Graft-Versus-Host Disease With Less Side Effects Through Altering T-Cell Differentiation - Wang, Qing Ya; Liu, Hui Hui; Dong, Yu Jun; Liang, Ze Yin; Yin, Yue; Liu, Wei; Wang, Qing Yun; Wang, Qian; Sun, Yu Hua; Xu, Wei Lin; Han, Na; Li, Yuan; et al. (Frontiers in Immunology, 2022)
Objective Previous studies showed that hypomethylating agents (HMAs) could alleviate acute graft-versus-host disease (aGvHD), but affect engraftment after allogeneic hematopoietic stem cell transplantation (allo-HSCT). The combination of two different HMAs in lower doses might overcome this problem. This study aimed to evaluate the treatment effect of the combination of two HMAs—azacitidine (5-Aza) and histone H3K27 methyltransferase inhibitor 3-deazaneplanocin (DZNep)—for the prophylaxis of aGvHD after allo-HSCT and to explore the possible mechanisms. Methods We first optimized the concentrations of individual and combinational 5-Aza and DZNep treatments to ensure no obvious toxicities on activated T cells by evaluating T-cell proliferation, viability, and differentiation. A mouse model of aGvHD was then established to assess the prophylactic efficacy of 5-Aza, DZNep, and their combination on aGvHD. The immunomodulatory effect on T cells and the hematopoietic reconstruction were assessed. Additionally, RNA sequencing (RNA-seq) was performed to identify the underlying molecular mechanisms. Results Compared with single treatments, the in vitro application of 5-Aza with DZNep could more powerfully reduce the production of T helper type 1 (Th1)/T cytotoxic type 1 (Tc1) cells and increase the production of regulatory T cells (Tregs). In an allo-HSCT mouse model, in vivo administration of 5-Aza with DZNep could enhance the prophylactic effect for aGvHD compared with single agents. The mechanism study demonstrated that the combination of 5-Aza and DZNep in vivo had an enhanced effect to inhibit the production of Th1/Tc1, increase the proportions of Th2/Tc2, and induce the differentiation of Tregs as in vitro. RNA-seq analysis revealed the cytokine and chemokine pathways as one mechanism for the alleviation of aGvHD with the combination of 5-Aza and DZNep. Conclusion The combination of 5-Aza and DZNep could enhance the prophylactic effect for aGvHD by influencing donor T-cell differentiation through affecting cytokine and chemokine pathways. This study shed light on the effectively prophylactic measure for aGvHD using different epigenetic agent combinations.